The Beetle: A Mystery - Marsh, Richard, 1857-1915 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Beetle: A Mystery" by Richard Marsh is a Gothic horror novel published in 1897. A shape-shifting ancient Egyptian entity arrives in London seeking vengeance against a British politician, Paul Lessingham. Through mesmerism and terror, the creature manipulates innocent victims to further its dark purpose. Told through four different narrators, the story weaves together mystery, supernatural horror, and psychological control as the Beetle pursues its prey through Victorian London, threatening everyone connected to its target. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Beetle_(novel)
Release date is 2004-02-01
Charles Franks and the Online Distributed Proofreading Team
Keywords: Horror tales; London (England) -- Fiction; Revenge -- Fiction; Monsters -- Fiction; Politicians -- Fiction; British -- Egypt -- Fiction; Egyptologists -- Fiction; Egypt -- Antiquities -- Collection and preservation -- Fiction; Paranormal fiction; Champnell, Augustus (Fictitious character) -- Fiction